Methionine addition to weanling pig diets - Tze-chow Ong; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1984)
Three growth trials and two metabolism trials utilizing 236 pigs were conducted to evaluate the effects of amino acids additions to weanling pig diets and to estimate the methionine requirement of weanling pigs using growth and nitrogen retention as criteria. From these results, it was concluded that the total sulfur amino acid requirement of weanling pigs does not exceed 0.56% of the diet. Addition of methionine to a lysine supplemented 18% protein corn or sorghum-soybean meal did not improve pig performance.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Methionine; Weanling pigs